Conserved quantities in Stokes flow with free surfaces - Cummings, L; Howison, S; King, JR (1997)
We derive an infinite set of invariants for two-dimensional Stokes flow with a free surface, driven by a point sink, in the case that surface tension effects are negligible. The complex variable methods used are closely related to those used for certain Hele-Shaw flows, which likewise have infinitely many conserved quantities. © 1997 American Institute of Physics.